Amalan Pengambilan Ibu Susuan:Satu Kajian Sorotan Tebhadap Dokumentasi Bukti Penyusuan - Siti Fatimah, Salleh; Normadiah, Daud (2014)
Patterns of community life are constantly changing over time and wave technology. It demands people restrict their lives through fiqhiyyah (Saddu al-Zara t). The same thing also happened in breast milk implementation in society. In line with the application of the method, an effective mechanism has to be adopted as proof of mother milk intake according to Islamic requirements. This is because Islamic law sets rules mechanism of milk suckling mahrams that is through testimony and confession. The objective of writing this article is to discuss issues related to milk suckling mahrams such the breast milk, baby age, the milk, the effect of breastfeeding, breastfeeding forms and mechanisms convict ban incest conviction milk In order to achieve this objective, we used method, namely library research. The finding of the study shows that breast feeding by documenting evidence from certain parties such as the National Registration Department is a very important step in harmonizing the system of the Muslim family.